Short-term effects of foot surgery on walking-related pain, function, and satisfaction in patients with Charcot–Marie–Tooth disease: a prospective cohort study - Basini, Giacomo; Rambelli, Chiara; Galletti, Martina; Zerbinati, Paolo; Prati, Paolo; Mascioli, Francesca; Masiero, Stefano; Mazzoli, Davide; Merlo, Andrea (Frontiers in Neurology, 2024)
Introduction Patients with Charcot–Marie–Tooth disease (CMT) often suffer from walking-related pain (WRP), muscle weakness, foot deformities, and reduced ankle dorsiflexion (DF), which affects their ability to walk and daily activities. Functional surgery (FS) can restore foot deviations, affecting the loading ability during gait. We assessed the short-term effects of FS in patients with CMT on WRP, foot and ankle structure, and function, along with patients’ perceived improvement. Methods This is a prospective cohort study on CMT patients who had undergone FS and rehabilitation. We analyzed the changes after 1 month, focusing on WRP, DF, the center of pressure progression (COPP) during walking, and measures of walking ability. The non-parametric Wilcoxon test was used. Results Ten patients were included. One month after FS, WRP reduced from 5.5 (IQR = 3.5) to 2 (IQR = 3.5), p = 0.063, with an effect size of 0.615. The highest decrease was found in patients with very high pre-surgical pain levels. DF almost reached 10° for both active and passive movements (p < 0.05), and COPP improved from 44 to 60% (p = 0.009) of foot length. Gait speed, lower limb functioning, and balance did not change. More than half of the sample felt improved or much improved after FS. Conclusion FS can be effective in reducing WRP and restoring foot posture in CMT patients in the short-term, which allows them to wear shoes, and leads to a perceived improvement and satisfaction. Lack of improvement in functional skills may be due to muscle weakness typical of CMT. Studies with longer follow-ups may confirm these hypotheses.